Critical Theories of Kaifi (According to Kaifiyah) - Ali, Hala Ameena (Makhz (Research Journal), 2024)
Pandit Brij Mohan Dattatreya Kaifi is a well-known Urdu researcher, critique and linguistic. He proposed his critical opinions about linguistics and poetry in the book “Kaifiyah”. He believes on objective, scientific and logical criticism and these perspectives reflects his own theoretical and practical critics. Social perspective reflects in his critical theories and writings. He has a full grip on the fields of his discussion for instance linguistics, grammar and the poetics of poetry. His critical writing style is logical, objective and easy to understand. He builds his own concepts of view by emerging the traditional rules and modern methods. He doesn’t believe to follow a specific school of thought about any argument; instead, he develops his own opinion by keeping the aspects of multiple schools of thoughts in his eyes.